DESIGN AND DEVELOPMENT OF ENERGY EFFICIENT GREEN IOT MODEL (International Journal of Food and Nutritional Sciences, 2022)
5G Green IoT is an energy-efficient process connected devices for the purpose of reducing power consumption, the greenhouse effects, and minimizing the emission of CO2. By using green computational units, communication protocols, and network-based architectures with maximum utilization of bandwidth and relatively low energy utilization. The essential element of Green IoT is sustainable design and energy-efficient. Wireless Communication System the previous four generations of cellular technology have each been a major paradigm shift that has broken backward compatibility. So we expect that 5G will be a paradigm shift that includes very high carrier frequencies with massive bandwidths, extreme base station and device densities new 5G air interface and spectrum together with LTE and WiFi to provide universal high-rate coverage and a seamless user experience. To support this, the core network will also have to reach unprecedented levels of flexibility and intelligence, spectrum regulation will need to be rethought and improved, and energy and cost efficiencies will become even more critical considerations. In this thesis we discuss the new thoughts which would improve the efficiency like using mm-waves, small cell, and smart antenna. Then we discuss some of the emerging applications based on 5G Wireless Communication System. In addition, we mentioned some challenges and open issues related to the previous generations and infrastructure boundaries that we have to considerate during designing 5G Device-to-Device Communication System networks. Just a few years ago mm wave was not being put to use because few electronic components could receive millimeter waves. Now, thanks to new technologies, it is on the brink of being an integral part of the next-generation network. Even with the advances of 4G LTEA, the network is running out of bandwidth. The solution, as seen by 5G wireless network developers, is to add more bandwidth by using frequency spectrum in the millimeter-wave frequency range. With hundreds of megahertz of wireless transmission bandwidth available at center frequencies such as 24, 28, and 38 GHz, 5G wireless networks will be capable of almost zero-latency phone calls and extremely high data speeds working on 5G network solutions typically refer to the mmWave frequency range as starting at about 24 GHz. The amount of bandwidth available at mmWave frequencies is enormous compared to the amount of frequency spectrum used by 4G and previous wireless network technologies. The architecture of 5G networks will be much different than earlier wireless-network generations, in part because of the use of mmWave frequencies. Smaller antennas will be used in mobile handsets to transmit and receive those higher-frequency signals the propagation distances for mmWave frequencies is less than for signals at the lower frequencies traditionally used in cellular networks.